How to Increase the Intention on Purchase at Agoda Through Perceived Value and E-Wom - Hendy Tannady; Angelina Theodora Ratna Primantina (Sigmagri, 2023)
One of the pursuits or pastimes people engage in to satisfy their obligations for work, play, or other reasons is travel. Due to unreliable customer support, bookings made by clients are abruptly canceled, and promises of money back that are never kept, Agoda has gotten multiple negative evaluations from its users. Negative evaluations with 1 and 2 stars are frequently the result of issues with payment, service, and reservation dates. The methodology employed in this study involves selecting 154 respondents by nonprobability sampling and judgmental sampling. Distribution of questionnaires with sample data received from up to 150 respondents and processed using SmartPLS is how data is collected. The results of this study show a significant effect, specifically that E-WOM has a significant positive effect on perceived value, perceived risk, and purchase intention, and that price sensitivity has a significant positive effect on perceived value, perceived risk, and perceived value without having a significant positive effect on purchase intention.